2010
DOI: 10.1371/journal.pone.0013926
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics-Based Modeling Defines the Regulatory Mechanism Underlying Aberrant EGFR Signaling

Abstract: BackgroundMutation of the epidermal growth factor receptor (EGFR) results in a discordant cell signaling, leading to the development of various diseases. However, the mechanism underlying the alteration of downstream signaling due to such mutation has not yet been completely understood at the system level. Here, we report a phosphoproteomics-based methodology for characterizing the regulatory mechanism underlying aberrant EGFR signaling using computational network modeling.Methodology/Principal FindingsOur pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
1
10
0
1
Order By: Relevance
“…This is functionally similar to simulated effects of a Y992F mutation (figure 3b-fourth row). These simulation results are consistent with previous experimental studies on both scenarios, in that SHP2 is needed for activation of the ERK pathway [39,41,42], and that expression of the Y992F EGFR mutant leads to sustained EGF-induced ERK activity [43]. We found that the catalytic efficiency (k cat /K m ) for SHP2 had to be on the order of 100 s 21 nM 21 to have an appreciable effect on site-specific phosphorylation levels (results in figure 3b are for 1000 s 21 nM…”
Section: Analysis Of Shp2supporting
confidence: 91%
“…This is functionally similar to simulated effects of a Y992F mutation (figure 3b-fourth row). These simulation results are consistent with previous experimental studies on both scenarios, in that SHP2 is needed for activation of the ERK pathway [39,41,42], and that expression of the Y992F EGFR mutant leads to sustained EGF-induced ERK activity [43]. We found that the catalytic efficiency (k cat /K m ) for SHP2 had to be on the order of 100 s 21 nM 21 to have an appreciable effect on site-specific phosphorylation levels (results in figure 3b are for 1000 s 21 nM…”
Section: Analysis Of Shp2supporting
confidence: 91%
“…New proteomic methods can measure additional proteins at virtually no additional cost, and proteomic datasets are starting to provide data-rich environments with measurements of all proteins in a system. SILAC technology has recently been used for time-series measurements of 147 proteins (Tasaki et al , 2010) in NIH3T3-derived cells, and again for time-series of 534 proteins in the cytosol and 626 proteins in the nucleus in glucocorticoid-exposed myogenic cells (Reeves et al , 2009). Most proteomic studies have not been performed with time-series repeats for studying dynamics, but large-scale dynamic data will become increasingly available with the explosive growth in the number of proteomic experiments (Zhang et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, phosphoproteomics-based approaches have first been applied to reveal the molecular mechanisms governed by tyrosine phosphorylation in response to external growth factors such as EGF [10,11,44,45], fibroblast growth factor (FGF) [46] or heregulin (HRG) [47]. Schulze et al identified interaction partners of the four members belonging to the ErbB receptor family (EGFR, ErbB2, ErbB3 and ErbB4) using the corresponding synthetic peptides as baits in an unbiased proteomic manner [45].…”
Section: Phosphoproteome Dynamics In Cancer Cellsmentioning
confidence: 99%